Fresno Merced Counties Legal Services Office Holiday Party - Watkins, Howard::::::::: (1982)
Office Christmas tree, Howard Watkins dressed as Santa Claus holding baby Robin Watkins with several young children, Marilyn Williams on floor; in background: Christine Watkins, ?